Using the carrier-envelope phase to control strong-field dissociation of HeH+ at midinfrared wavelengths - Ursrey, D.; Esry, B. D. (My University, 2017)
We study the response of HeH+ to an intense, few-cycle laser pulse. Specifically, we present the carrier-envelope phase (CEP) dependence of the kinetic-energy-release spectrum, the spatial asymmetry, and the total dissociation probability in two-cycle pulses with an intensity of 1014W/cm2 and wavelengths of 3200 and 4000 nm. Strong spatial asymmetries are found in spite of the fact that the electron always becomes localized as He+H+, demonstrating that control of such asymmetries can be obtained via control of the nuclear degrees of freedom—as opposed to its usual interpretation as control over the electronic degrees of freedom. We explain these CEP effects in terms of our photon-phase representation.